(untitled) (International Seven Journal of Multidisciplinary, 2024)
The purpose of this paper is to analyze the characteristics of the financial education of students at two higher education institutions in the State of Mexico. It was found that Institution 2 is in a better position with respect to Institution 1 by presenting more favorable aspects in 3 of the 5 variables analyzed, however, it is also deduced that the students surveyed in both schools present a low level of financial education by presenting a lack of knowledge and skills in the variables studied and in addition to showing negative aspects that could put their financial situation at risk.